2006
DOI: 10.1001/archinte.166.20.2260
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of Tamoxifen for Breast Cancer Prevention by Primary Care Physicians

Abstract: A minority of primary care physicians have prescribed tamoxifen for breast cancer prevention. The decision to prescribe tamoxifen is affected by the ability to determine eligibility, patient demand, and personal experience with breast cancer as much as perceptions of the risks and benefits. A woman's risk of endometrial cancer from tamoxifen seems to have less impact on prescribing decisions than the magnitude of her breast cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 27 publications
1
62
0
Order By: Relevance
“…Use of cancer chemopreventive agents is difficult to measure as these drugs all have other indications and the indications for use are not routinely recorded in drug databases. Several studies of tamoxifen and raloxifene use for breast cancer chemoprevention show that neither drug is being widely used by physicians or women at increased risk for breast cancer (19)(20)(21)(22)(23)(24)(25). Although aspirin is commonly used for cardiovascular disease prevention (26), its use for colorectal cancer prevention is also not known.…”
Section: Discussionmentioning
confidence: 99%
“…Use of cancer chemopreventive agents is difficult to measure as these drugs all have other indications and the indications for use are not routinely recorded in drug databases. Several studies of tamoxifen and raloxifene use for breast cancer chemoprevention show that neither drug is being widely used by physicians or women at increased risk for breast cancer (19)(20)(21)(22)(23)(24)(25). Although aspirin is commonly used for cardiovascular disease prevention (26), its use for colorectal cancer prevention is also not known.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies described how women or physicians make decisions to use medications to reduce risk for primary breast cancer (Appendix Table 2, available at www .annals.org) (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76). In an interview-based, cross-sectional study after an educational session about indications and adverse effects of tamoxifen, women indicated that breast cancer (69%), pulmonary embolism (67%), endometrial cancer (63%), and deep venous thrombosis (58%) were "very important" in making their decisions about use (69).…”
Section: Surveys Of Medication Decisions and Concordancementioning
confidence: 99%
“…Of 350 physicians responding to a mailed survey, 27% had prescribed tamoxifen for breast cancer risk reduction within the previous 12 months (65). Prescribers were more likely than nonprescribers to have a family member with breast cancer (20% vs. 9%) and believed that the benefits of tamoxifen outweigh the risks (63% vs. 39%), colleagues are prescribing it (33% vs. 17%), it is easy to determine who is eligible (28% vs. 11%), and many female patients ask for information about it (15% vs. 5%).…”
Section: Surveys Of Medication Decisions and Concordancementioning
confidence: 99%
“…Primary care clinicians have generally been unenthusiastic about tamoxifen for chemoprevention given its original use by oncologists in breast cancer treatment, combined with concerns about serious adverse events. 61,62 As a result, many women who were at increased risk of developing breast cancer were not considered to be candidates for tamoxifen chemoprevention therapy and were not offered risk-reduction therapy.…”
Section: Use Of Serms In Clinical Practicementioning
confidence: 99%